Organizational Change as Discourse: Communicative Actions and Deep Structures in the Context of Information Technology Implementation - Heracleous, Loizos; Barrett, Michael (Academy of Management Journal, 2001)
The authors conceptualize discourse as a duality of communicative actions and deep structures, mediated by the modality of interpretive schemes, and develop a discourse analysis methodology based on the fields of hermeneutics and rhetoric. They then explore the role of discourse in shaping organizational change processes through its influence on actors' interpretations and actions, using a longitudinal field study of electronic trading implementation in the London Insurance Market. The authors conclude with some theoretical and practical contributions on discourse-practice links, the illumination of multiple perspectives in change processes, and implications for electronic data interchange implementation.